Using Scramble Game To Develop English Vocabulary Of Grade Seven Students At SMP Negeri 1 Pematangsiantar - Carolin Panjaitan; David Berthony Manalu; Siska Anggita Situmeang (CV Putra Publisher, 2023)
The objectives of this research was find out whether the using scramble game to develop English vocabulary of grade seven students at SMP Negeri 1 Pematangsiantar. This research used quantitative research with a quasi-experimental research design. The population of this study was the VII grade students of SMP Negeri 1 Pematangsiantar with a total of 352 students. The sample of this study was divided into two classes, class VII-7 as the control class consisting of 32 students who used the conventional media and class VII-8 as the experimental class consisting of 32 students who used scramble game. Data collection instruments used multiple choice for pre-test and post-test. The data analysis technique used in this research is SPSS version 21, by conducting normality test, homogeneity test and hypothesis test. In the post-test results for the experimental class, the average was 79.68, while in the control class the average was 74.53. Based on the hypothesis test using an independent test, it shows a sig (2-tailed) value of 0.016 < 0.05, then Ha is accepted and Ho is rejected. Therefore, it can be concluded that the use of scramble game can improve the English vocabulary of grade seven students at SMP Negeri 1 Pematangsiantar.